Transisi Menuju Sistem Perpajakan Digital: Tinjauan Hukum Atas Praktik Joki Dalam Coretax - Aryanti Agripina WInata; Gunardi Lie (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
The transition toward a digital tax administration system in Indonesia through the implementation of Coretax represents a strategic reform aimed at enhancing administrative efficiency, transparency, and taxpayer compliance within a self assessment framework. However, the emergence of intermediary practices commonly referred to as tax jockey services reflects structural and normative deficiencies in regulating third party access and digital accountability. This study employs a normative doctrinal legal method using statute and conceptual approaches to examine the legal construction governing digital taxation and its implications for unauthorized delegation practices. The analysis identifies regulatory gaps within Law Number 7 of 2021 and Law Number 28 of 2007, particularly concerning the absence of explicit limitations on informal representation, as well as insufficient integration with personal data protection principles under Law Number 27 of 2022. Furthermore, the findings reveal that weak authentication mechanisms and limited digital literacy contribute to systemic vulnerabilities that enable misuse of sensitive taxpayer data. This study proposes a normative reconstruction emphasizing stricter legal boundaries on third party involvement, strengthened digital authentication protocols, and integrative regulatory harmonization to ensure legal certainty, data protection, and sustainable taxpayer compliance.